2018
DOI: 10.18203/2394-6040.ijcmph20184566
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glycaemic control in patients with type 2 diabetes: a clinic-based study in a slum of Kolkata

Abstract: Background: Although diabetes is a chronic condition, it can be controlled and managed to prevent complications. Long-standing diabetes with poor glycaemic control leads to many complications. This study aims to assess the glycaemic control status and its associated factors among type 2 diabetes patients attending Urban Health Centre in a slum of Kolkata, West Bengal.Methods: A clinic-based cross-sectional study was conducted among 184 diabetic patients attending clinic at Urban Health Centre, Chetla from Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
2
9
1
Order By: Relevance
“…The prevalence of inadequate & poor glycemic control status was comparable to previous studies conducted in Saudi Arabia (74.9%) [28], Ghana (70%) [32], Uganda (73.52%) [33] and Northeast Ethiopia (70.8%) [11]. However, the magnitude of inadequate and poor glycemic control status in the current study was greater than previously reported in the United States (69%) [34], India (37.5%) [27], Tanzania (49.8%) [35], North West Ethiopia (60.5%) [36], Addis Ababa, Ethiopia (68.3%) [10] and East Ethiopia (45.2%) [6]. The higher proportion of poor glycemic control in the present study than previous studies conducted in parts of the country could be that patients seeking advanced treatment were referred to the Tikur Anbessa Specialized Hospital.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The prevalence of inadequate & poor glycemic control status was comparable to previous studies conducted in Saudi Arabia (74.9%) [28], Ghana (70%) [32], Uganda (73.52%) [33] and Northeast Ethiopia (70.8%) [11]. However, the magnitude of inadequate and poor glycemic control status in the current study was greater than previously reported in the United States (69%) [34], India (37.5%) [27], Tanzania (49.8%) [35], North West Ethiopia (60.5%) [36], Addis Ababa, Ethiopia (68.3%) [10] and East Ethiopia (45.2%) [6]. The higher proportion of poor glycemic control in the present study than previous studies conducted in parts of the country could be that patients seeking advanced treatment were referred to the Tikur Anbessa Specialized Hospital.…”
Section: Discussionsupporting
confidence: 76%
“…The questionnaire was developed based on various similar previous studies [18,[25][26][27][28] and was further modified to include important variables from this study [see Additional file 1]. It was initially prepared in English, translated into Amharic, the local language, and retranslated into English again to ensure consistency.…”
Section: Data Collection Tools Questionnairementioning
confidence: 99%
“…(7) However, in the current study, gender or age were not found significant determinants for poor glycaemic control similar to other studies done in elsewhere in India. (8,9,10) The proportion of diabetics who performed exercise was low (12%) in our study. This was similar to other studies among diabetics which found high proportion (56%) of urban diabetics to be physically inactive.…”
Section: Discussioncontrasting
confidence: 50%
“…Similarly, positive association between smoking and diabetes have been found in communitybased studies among diabetics. (8,14) In our study, overall, 76% were compliant to medications and gave no history of missing tablets. This is similar to the compliance rate seen in another study among diabetics in rural Tamil Nadu and Bangalore.…”
Section: Discussionmentioning
confidence: 58%
“…Studies have analysed socio-economic inequality in the prevalence of diabetes but left the gender differential analysis in its prevalence across different socio-economic groups 18 , 19 . Few other studies have focused either on a single state or the geographical variation in the prevalence of diabetes in the country 20 22 .…”
Section: Introductionmentioning
confidence: 99%